Study on Induced Draft Fan Fault Warning of Thermal Power Unit Based on Big Data Analysis - AN Jizhen; ZHENG Fuhao; LIU Yifan; CHEN Heng; XU Gang (发电技术)
Aiming at the frequent occurrence of induced draft fan faults in thermal power units, a kind of induced draft fan fault warning method based on big data analysis was proposed.Taking the induced draft fan of a 330 MW thermal power unit as the research object, 11 kinds of characteristic information closely related to its working state were extracted. After data pretreatment, a state prediction model of the induced draft fan was established based on BP neural network, and its error met the requirements of engineering. Using distributed control system (DCS) and safety instrumentation system (SIS), a set of induced draft fan state warning system was designed, and the visual interface of this warning system was developed. When the measured value of a certain feature information exceeds the safety threshold of the predicted value of the model, the system will remind the operator to carry out maintenance and troubleshooting, so as to realize an effective early warning of the induced draft fan fault.